A novel high-speed sense-amplifier-based flip-flop. - Strollo, A.G.M.
A new sense-amplifier-based flip-flop is presented. The output latch of the proposed circuit can be considered as an hybrid solution between the standard NAND-based set/reset latch and the NC-2MOS approach. The proposed flip-flop provides ratioless design, reduced short-circuit power dissipation, and glitch-free operation. The simulation results, obtained for a 0.25-μm technology, show improvements in the clock-to-output delay and the power dissipation with respect to the recently proposed high-speed flip-flops. The new circuit has been successfully employed in a high-speed direct digital frequency synthesizer chip, highlighting the effectiveness of the proposed flip-flop in high-speed standard cell-based applications.
Keywords: 0.25 micron; CMOS digital integrated circuits; Clock-to-output delay; Glitch-free operation; High-speed direct digital frequency synthesizer chip; High-speed flip-flop.; Sense amplifiers; Set-reset latches; Short-circuit power dissipation reduction